2020
DOI: 10.1029/2019jc015696
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Pacific Sector of the Southern Ocean to Wind Stress Variability From 1995 to 2017

Abstract: Drifter, satellite, expendable bathythermograph (XBT), and Argo float data are used to study the response of the Pacific Sector of the Southern Ocean (PSSO) to the wind stress field in the period 1995-2017, in terms of eddy field, water mass transport, and heat fluxes at large and regional scales. Increasing wind stress over the PSSO in those two decades led to a growth of the Eddy Kinetic Energy (EKE) in the region of the Antarctic Circumpolar Current (ACC). Increases of the EKE occur with delays of 1-4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 77 publications
3
14
0
Order By: Relevance
“…We first consider the relationship between EKE and wind stress. We find the change in EKE generally lags by 0–46 months changes in the wind stress (Figures 2b–2d), which is consistent with previous studies (e.g., Patara et al., 2016; and Menna et al., 2020). It is worth noting that the correlations and lags between EKE and wind stress are slightly sensitive to the wind product and window length chosen to define the mean (i.e., using 3, 4, 6, and 12 months of running averages as presented in Figure S1 of Supporting Information and Table ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We first consider the relationship between EKE and wind stress. We find the change in EKE generally lags by 0–46 months changes in the wind stress (Figures 2b–2d), which is consistent with previous studies (e.g., Patara et al., 2016; and Menna et al., 2020). It is worth noting that the correlations and lags between EKE and wind stress are slightly sensitive to the wind product and window length chosen to define the mean (i.e., using 3, 4, 6, and 12 months of running averages as presented in Figure S1 of Supporting Information and Table ).…”
Section: Resultssupporting
confidence: 92%
“…For example, Hogg et al (2015) found that the two fields are well correlated with each other in the Indian and Pacific sectors of the Southern Ocean using satellite altimeter records and suggested that the long-term change of EKE is primarily controlled by local wind stress. Menna et al (2020) also found a high correlation between EKE and wind stress in the Pacific sector. Based on numerical Abstract Previous studies proposed that the increase in the eddy kinetic energy (EKE) in the Southern Ocean in recent decades is primarily caused by the strengthening of circumpolar surface westerlies.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Mesoscale eddies are detected everywhere in the ocean [15,16] and dominate the kinetic energy [17,18]. They can influence the global ocean circulation at all the scales, the mixing processes as well as the transport of water masses, heat, salt, and substances at great distance from the formation area.…”
Section: Introductionmentioning
confidence: 99%